ANALISIS PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP MATA PELAJARAN STRUKTUR BETON BERTULANG - Satria Arya Wigunha (Jurnal Salome : Multidisipliner Keilmuan, 2024)
One learning model that focuses on High Order Thinking Skills (HOTS) is a project-based learning model. This model involves students participating in solving problems in several structured stages, both individually and in groups. This research aims to analyze the impact of project-based learning (PJBL) on teaching Structural Reinforced Concrete (SBB) in an educational context. This research focuses on the influence of PBL on student learning, especially in terms of understanding practical problems, understanding knowledge, and improving practical and problem-solving abilities. The study also explores cultural differences in educational approaches, emphasizing the importance of project-based learning in Asian countries, where educational cultures emphasize discipline, order, and respect for teachers. This research further examines the impact of PBL on student learning in various subjects, such as engineering and technology disciplines, and the benefits of PBL in developing practical skills and an innovative spirit. This research also discusses the specific process of project-based learning, including identifying the goals and scope of the project, as well as the teacher's role in providing support and guidance. The findings of this study will contribute to the understanding of the effectiveness of PBL in SBB teaching and provide insight into the potential application of PBL in other educational contexts.